Subspace Search Method for Quadratic Programming with Box Constraints (Journal of Computational Mathematics, 1999)
A subspace search method for solving quadratic programming with box constraints is presented in this paper. The original problem is divided into many independent subproblem at an initial point, and a search direction is obtained by solving each of the subproblem, as well as a new iterative point is determined such that the value of objective function is decreasing. The convergence of the algorithm is proved under certain assumptions, and the numerical results are also given.
Keywords: Subspace search method; Quadratic programing; Matrix splitting.